2021
DOI: 10.1051/parasite/2021035
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Toxoplasma IgG assays: What performances for what purpose? A systematic review

Abstract: Chronic infection with Toxoplasma gondii is attested by the detection of specific anti-Toxoplasma IgG. A wide panel of serologic methods is currently marketed, and the most suitable method should be chosen according to the laboratory resources and the screened population. This systematic review of evaluation studies aimed at establishing an overview of the performances, i.e. sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of marketed anti-Toxoplasma IgG assays, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Thus, as already shown by Simon et al, we observed that reactivity against the GRA8 antigen led to falsepositive results [30]. Simon et al hypothesize that past contact with Neospora caninum and Hammondia hammondi, two parasites close to T. gondii, could explain false-positive results with ARCHITECT-IgG and IB-recomLine, mostly due to crossreaction with GRA8 (used by both ARCHITECT and IB-recomLine) and also GRA7 to a lesser extent (only used by IB-recomLine) [26]. Therefore, IB-recomLine could result in false-positive IgG detections and bias the determination of immune status.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, as already shown by Simon et al, we observed that reactivity against the GRA8 antigen led to falsepositive results [30]. Simon et al hypothesize that past contact with Neospora caninum and Hammondia hammondi, two parasites close to T. gondii, could explain false-positive results with ARCHITECT-IgG and IB-recomLine, mostly due to crossreaction with GRA8 (used by both ARCHITECT and IB-recomLine) and also GRA7 to a lesser extent (only used by IB-recomLine) [26]. Therefore, IB-recomLine could result in false-positive IgG detections and bias the determination of immune status.…”
Section: Discussionmentioning
confidence: 59%
“…Determining the immune status is essential in three main situations: pregnant women, immunocompromized patients and transplant recipients or donors [26]. For pregnant women, detection of specific IgG antibodies without IgM detection at the beginning of pregnancy indicates a past infection and rules out the risk of a congenital primary infection [21].…”
Section: Introductionmentioning
confidence: 99%
“…According to the manufacturer, the relative sensitivity of this immunoassay ranges from 99.5 to 100.0% [lower 95% confidence interval (CI): 97.6-99.1%], and the relative specificity of the immunoassay ranges from 98.8 to 100.0% [lower 95% confidence interval 95% CI: 96.8-99.2%] [13]. Moreover, a recent systematic review and meta-analysis of assays for detecting anti-Toxoplasma IgG revealed a mean sensitivity level of 98.6% (95% CI: 97.5-100), a mean specificity level of 99.6% (95% CI: 98.7-100), a mean positive predictive value of 99.2% (95% CI: 98.3-100) and a mean negative predictive value of 99.4% (95% CI: 98.7-100) for Elecsys® Toxo IgG assay, with 100% concordance with the dye test for sera with interfering diseases [14].…”
Section: Methodsmentioning
confidence: 93%
“…Производительность этих тестов варьируется в достаточно широких пределах. Так, при сравнении 17 различных публикаций при исследовании на IgG к T. gondii чувствительность тестов составляла от 89,7% до 100%, а специфичность -от 91,3% до 100% [8].…”
Section:  результаты и обсуждениеunclassified